2022
DOI: 10.3390/ma15165655
|View full text |Cite
|
Sign up to set email alerts
|

Friction Modelling for Tube Hydroforming Processes—A Numerical and Experimental Study with Different Viscosity Lubricants

Abstract: The final quality of sheet and tube metal–formed components strongly depends on the tribology and friction conditions between the tools and the material to be formed. Furthermore, it has been recently demonstrated that friction is the numerical input parameter that has the biggest effect in the numerical models used for feasibility studies and process design. For these reasons, industrial dedicated software packages have introduced friction laws which are dependent on sliding velocity, contact pressure and som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Under the boundary lubrication condition, the friction coefficient is composed of solid and fluid friction coefficients. The local heating effect of the friction at the peak causes the viscosity of the lubricant to decrease, resulting in a decrease in the coefficient of fluid friction [15,16]. The effect of variability on material properties was further analyzed by Harsch et al [17,18], who concluded that material fluctuations contributed significantly to the forming process.…”
Section: Introductionmentioning
confidence: 99%
“…Under the boundary lubrication condition, the friction coefficient is composed of solid and fluid friction coefficients. The local heating effect of the friction at the peak causes the viscosity of the lubricant to decrease, resulting in a decrease in the coefficient of fluid friction [15,16]. The effect of variability on material properties was further analyzed by Harsch et al [17,18], who concluded that material fluctuations contributed significantly to the forming process.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are ongoing efforts to develop friction models that specifically aim to accurately quantify the nonlinear friction observed at the tube-die interface. A variable friction law that takes into account the sliding velocity, contact pressure and viscosity was developed and implemented in the commercial software Abaqus [16] Another critical design aspect of THF is preforming. Depending on the shape complexity of the tubular part and formability of the tubular material, the incoming straight tube might need to be bent or crushed before the final THF process is carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The material parameters include mechanical properties of tube material, such as elongation, tensile strength, strain hardening rate, etc., while process parameters represent the load path which is, generally speaking, the loading of internal pressure and the amount of axial feeding. Also, the die's geometric configuration and the status of the lubrication at the specimen -die interface have significant impact on the outcome [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…One of the significant parameters that influence the quality of the product is the amount of friction between the die and the specimen during the hydroforming process. The friction at the specimen-die interface usually causes a nonuniform distribution in terms of shear stress, as well as variation in the thickness of the formed product along its length [11,[20][21][22]. The degree to which the friction is present depends on the geometrical features and the loading conditions between moving surfaces since hydroforming is an active process of deformation in different directions.…”
Section: Introductionmentioning
confidence: 99%